Islam dan Liberalisme: Antara Maṣlaḥah dan Mafsadah: Islam and Liberalism: Between Benefit and Harm - A. Harris, Khalif Muammar (Afkar: Jurnal Akidah dan Pemikiran Islam, 2018)
Since the early 20th century the Muslim world, in particular, faced a great intellectual challenge which originated in the Western civilisation, i.e., the rise of Muslim intellectuals who adopted and promoted the secular-liberal ideas and values in the midst of Muslim societies. The decline of the Islamic civilisation followed by the colonialisation of Muslim countries, and the inferiority complex which accompanied it, had fostered this uncritical attitude towards Western thought and ideas. Some of these ideas are indeed good, benefecial and therefore acceptable throughout the world, however, some are harmful and destructive to the religion of Islam and the Muslim identity. This study attempts to explore and analyse the history and the complexities of liberalism as a philosophy and ideology, and to examine it from an Islamic point of view. It responds to the confusions and allegations raised by the protagonists of liberalism among Muslims. In order to grasp the correct understanding of liberalism and its implications upon Islamic faith and identity, a critical and analytical study is conducted to examine the ideas propagated by the thinkers and ideologues of liberalism. This study also explicates the views of Muslim scholars on these ideas and the proper attitude that Muslims must adopt to successfully face this intellectual challenge.